EFL UNDERGRADUATE STUDENTS' PERCEPTION OF USING CHATGPT TO DEVELOP WRITING SKILLS - Mustika, Dina; Alfian; Fitria, Wahyuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Writing is recognized as one of the most challenging skills in EFL contexts, requiring simultaneous management of grammar, vocabulary, and idea organization. The emergence of AI tools such as ChatGPT offers new possibilities for writing support. This study investigates EFL undergraduate students' perceptions of using ChatGPT as a learning tool for writing development, employing a mixed-method design. Quantitative data were collected through a 10-item questionnaire administered to 100 participants, and qualitative data were gathered via semi-structured interviews with 10 respondents. Guided by the Technology Acceptance Model (TAM), the study examined perceived usefulness, perceived ease of use, attitude toward use, and behavioral intention to use. Findings reveal strong positive perceptions across all TAM constructs, with students reporting benefits in grammar improvement, idea generation, writing organization, and quick feedback. Challenges include over-reliance, difficulty interpreting complex responses, and occasional inaccuracies. ChatGPT is best positioned as a supplementary writing aid under guided and critical conditions.